2017
DOI: 10.3892/etm.2017.4746
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin inhibits vascular adhesion molecule expression in TNF-α-stimulated vascular muscle cells

Abstract: Abstract. Atherosclerosis is a chronic inflammatory disease, which is associated with the increased expression of adhesion molecules in vascular smooth muscle cells (VSMCs). Cordycepin is one of the major bioactive components of Ophiocordyceps sinensis that has been demonstrated to exert anti-atherogenic activity; however, its molecular mechanisms are poorly understood. The aim of the present study was to examine the in vitro effects of cordycepin on the tumor necrosis factor (TNF)-α-induced suppression of adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Activation of inflammatory signalling cascades leads to translocation of NFĸB from the cytoplasm to the nucleus and binding to DNA. We found 11 papers reporting a cordycepin-mediated reduction in the nuclear levels of NFĸB [ 28 , 43 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. In contrast, two papers reported no changes in the nuclear localisation of NFĸB [ 72 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of inflammatory signalling cascades leads to translocation of NFĸB from the cytoplasm to the nucleus and binding to DNA. We found 11 papers reporting a cordycepin-mediated reduction in the nuclear levels of NFĸB [ 28 , 43 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. In contrast, two papers reported no changes in the nuclear localisation of NFĸB [ 72 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…In reviewing the impact of cordycepin on the phosphorylated level of Akt, the Ser 473 site was extensively studied (11 papers). Most studies (nine articles) demonstrated an inhibitory effect of cordycepin on Akt phosphorylation at Ser 473 [ 11 , 101 , 103 , 142 , 144 , 149 , 150 , 151 , 152 , 153 ]. Only one study found no effect [ 145 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further examined the effect of cordycepin on OSCAR, cathepsin K and MMP9 mRNA expression levels, where 1 μ M cordycepin significantly downregulated RANKL-induced OSCAR, cathepsin K and MMP activation (Figures 5(c) , 5(d) and 5(e) ). Plus, NFATc1 and cFOS activation were caused by MAPK (mitogen-activated protein kinases) signaling, which is required for early osteoclast differentiation [ 28 , 29 ]. To confirm the molecular mechanism of cordycepin effects on MAPKs following the activation of RANKL in RAW264.7 cells, we investigated the phosphorylation of p38, ERK and JNK using a western blot.…”
Section: Resultsmentioning
confidence: 99%
“…In a PDGF‐stimulated RAoSMCs model, cordycepin is shown to cause significant downregulation of MMP‐2, −9, and − 13 expressions (S. W. Yang, Lim, et al, 2015). In a separate study, cordycepin is shown to decrease the expression of VCAM‐1 and ICAM‐1 in TNF‐α‐stimulated human aortic vascular smooth muscle cells via downregulating the MAPK/Akt/NF‐κB signaling pathways (Yan et al, 2017).…”
Section: Anti‐inflammatory Activitymentioning
confidence: 99%